Comprehensive examination of the multilevel adverse risk and protective factors for cardiovascular disease among hypertensive African Americans. Issue 6 (24th May 2019) - Schoenthaler, Antoinette; Fei, Kezhen; Ramos, Michelle A.; Richardson, Lynne D.; Ogedegbe, Gbenga; Horowitz, Carol R.
Abstract: This paper describes the multilevel factors that contribute to hypertension disparities in 2052 hypertensive African Americans (mean age 52.9 ± 9.9 years; 66.3% female) who participated in a clinical trial. At the family level, participants reported average levels of life chaos and high social support. However, at the individual level, participants exhibited several adverse clinical and behavioral factors including poor blood pressure control (45% of population), obesity (61%), medication non‐adherence (48%), smoking (32%), physical inactivity (45%), and poor diet (71%). While participants rated their provider as trustworthy, they reported high levels of discrimination in the health care system. Finally, community‐level data indicate that participants reside in areas characterized by poor socio‐economic and neighborhood conditions (eg, segregation). In the context of our trial, hypertensive African Americans exhibited several adverse risks and protective factors at multiple levels of influence. Future research should evaluate the impact of these factors on cardiovascular outcomes using a longitudinal design.